2014
DOI: 10.1017/s0950268814002490
|View full text |Cite
|
Sign up to set email alerts
|

An explosive outbreak of Streptococcus pneumoniae serotype-8 infection in a highly vaccinated residential care home, England, summer 2012

Abstract: In August 2012, an explosive outbreak of severe lower respiratory tract infection (LRTI) due to Streptococcus pneumoniae serotype-8 occurred in a highly vaccinated elderly institutionalized population in England. Fifteen of 23 residents developed LRTI over 4 days (attack rate 65%); 11 had confirmed S. pneumoniae serotype-8 disease, and two died. Following amoxicillin chemoprophylaxis and pneumococcal polysaccharide vaccine (PPV) re-vaccination no further cases occurred in the following 2 months. No association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Twelve studies assessed whether case-patients had ever received either pneumococcal vaccine before the outbreak [ 62 , 66 , 67 , 71 , 73 , 74 , 82 , 88 , 89 , 91 , 93 , 97 ]. Of the studies that provided enough information to calculate vaccination coverage of the source population of cases, two reported 0% coverage [ 66 , 88 ], one reported 7% [ 89 ], and one reported 57% [ 93 ]. At least one vaccine failure was reported for 6 studies [ 71 , 74 , 88 , 91 , 93 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies assessed whether case-patients had ever received either pneumococcal vaccine before the outbreak [ 62 , 66 , 67 , 71 , 73 , 74 , 82 , 88 , 89 , 91 , 93 , 97 ]. Of the studies that provided enough information to calculate vaccination coverage of the source population of cases, two reported 0% coverage [ 66 , 88 ], one reported 7% [ 89 ], and one reported 57% [ 93 ]. At least one vaccine failure was reported for 6 studies [ 71 , 74 , 88 , 91 , 93 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that provided enough information to calculate vaccination coverage of the source population of cases, two reported 0% coverage [ 66 , 88 ], one reported 7% [ 89 ], and one reported 57% [ 93 ]. At least one vaccine failure was reported for 6 studies [ 71 , 74 , 88 , 91 , 93 , 97 ]. Two reports described one case-patient vaccine failure of a vaccine received within five years of the outbreak [ 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one British study did find the length of time after PPSV23 vaccination to be associated with pneumococcal pneumonia incidence in an elderly care home: affected residents developed the disease a median of 10.2 years (range: 7.3-17.9) after their last PPSV23 dose, compared with 7.2 years (range: 6.8-12.8) in unaffected residents. 19 Moreover, both Kawakami et al 14,20 and Ohshima et al 15 reported persistent immunogenicity following PPSV23 vaccination, lasting approximately seven years, but revaccination can induce comparable immunogenicity to the initial dose. Suzuki et al also reported that the efficacy of PPSV23 declines beyond 5 years after primary vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to create an awareness of pneumococcal revaccination, because pneumococcal pneumonia incidence and mortality among vaccinated person would be associated with time since the initial dose was administered. 19…”
Section: Discussionmentioning
confidence: 99%